Tingkat Inflasi,Investasi dan Ekspor terhadap Pertumbuhan Ekonomi di Negara Jerman 2004-2023 - Arief Hakim Permana; Eni Setyowati (JURNAL ILMIAH EDUNOMIKA, 2025)
The country's ability to manage its resources and the success or failure of the government's economic policies are reflected in economic growth. A nation's level of wealth and the well-being of its citizens are indicated by economic growth, which is typically gauged by the rise in GDP. Analysis of the impact of exports, investment, and inflation on Germany's economic development from 2004 to 2023 is the goal of this study. Multiple linear regression with partial and simultaneous tests is the methodology employed in this investigation. The World Bank provided data on exports, foreign direct investment, GDP, and inflation. According to the regression analysis's findings, GDP is significantly impacted by all three factors combined (p <0.05). Nevertheless, additional research reveals that only exports significantly and favorably impact GDP (p <0.05). The GDP increases by 0.026197% for every 1% rise in exports. On the other hand, GDP is not significantly impacted by either inflation or foreign direct investment (p > 0.05). These findings demonstrate how crucial exports were to Germany's economic expansion during the study period. Additional research is necessary to comprehend the contextual factors that might be involved in the negligible effects of inflation and foreign direct investment. Keywords : Inflation, FDI, Exports, GDP